pengembangan video pembelajaran pemeliharaan sasis dan pemindah tenaga kendaraan ringan - endra duwi_riadi (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
The aims of this research are (1) to develop learning video media to complete the PSPTKR subject module for class XI of Industrial Vocational High School Yogyakarta. (2) determine the feasibility of the PSPTKR subject practical learning video. This research is a research and development (Research and Development) with a 4D model. The subjects in this study were material experts, media experts and students of class XI TKR SMK Perindustrian Yogyakarta as users of the learning video media that was developed. The object of research is teaching materials. The collection technique uses a questionnaire/questionnaire, the instrument used is a measuring tool such as a questionnaire, observation guidelines and interview guidelines used by researchers to collect data in research, data analysis techniques using quantitative descriptive. The results of the research show that (1) the development of learning video products to complete the PSPTKR subject module can be done using the development of the four-D model consisting of the define, design, develop, disseminate, and (2) the development of learning videos that are suitable for use as teaching materials. , this is evidenced by the results of the percentage of material expert validation, which is 75.75% in the